Legal Aspect of Handling of Covid-19 Suspected Patients in Health Services in Hospital - Nur Azizah Sri Utami; Andika Persada Putera; Asmuni (Verdict: Journal of Law Science, 2022)
Hospitals function as quarantine, prevention and control of the Covid-19 Pandemic era. However, the crucial issue is the hospital is lying; patients who have not confirmed Covid-19 but are considered positive by the hospital. This study discusses legal protection for hospitals to care for patients with suspected Covid-19. The research is compiled with the type of normative juridical research; namely, research focused on examining the application of the rules or norms in positive law. The result shows that the hospital as a legal entity (recht person) has risks under Article 58 (1) of the Health Law, namely compensating for errors/omissions of doctors and health workers. According to the Vicarious Liability doctrine, the hospital is legally responsible for all losses caused by its subordinates. According to the Hospital Liability doctrine, the hospital is responsible for taking over the mistakes or omissions of the hospital. With the right of regress, the hospital will ask for compensation back to the doctor who made a mistake. The Strict Liability Doctrine states that the hospital is responsible for the workhouse. The implementation of hospital legal protection has yet to be precise. Supervision and guidance by the government, including the government’s authority on health, still need to be made clear. Medical audits could have gone better. Doctors have the right to obtain legal protection as long as they carry out their duties under professional standards and standard operating procedures under Article 50 of the Medical Practice Act.